Liza's Monday and Other Poems - Sellers, Bettie (Appalachian State University, 1986)
Published in 1986, Bettie Sellers's book of poems speaks for ordinary women whose lives have been confronted with unfortunate circumstances. Writing in a narrative and lyrical style, Sellers brings life to new stories and songs based on the downtrodden women she has encountered.